Question
upstudy study bank question image url

(c) \( g^{2} \frac{2 x}{2} \) Determine the numerical value of \( (3 x+p)^{2} \) if it is given that \( 9 x^{3}+y^{2}=12 \) and \( x y=-3 \) Given that \( m=x(x-y)^{2} \). Determine the value of \( m \) if \( x y^{2}=4 \) and \( x^{3}-2 x^{2} y=3 \)

Ask by Bush Murphy. in South Africa
Feb 21,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

Cannot determine the numerical value of \( (3x + p)^2 \) without knowing the value of \( p \). For \( m = x(x - y)^2 \), the value cannot be determined with the given information.

Solution

Sign in to Unlock Answers for Free!

A Learning Platform Trusted by Millions of Real Students and Teachers.

star-icon Unlock

Answered by UpStudy AI and reviewed by a Professional Tutor

Extra Insights

To solve for the numerical value of \( (3x + p)^2 \), we first need to find \( x \) and \( y \) from the given equations. From \( xy = -3 \), we can express \(y\) as \(y = -\frac{3}{x}\). Substituting \(y\) into the first equation \(9x^3 + y^2 = 12\), we get: \[ 9x^3 + \left(-\frac{3}{x}\right)^2 = 12 \\ 9x^3 + \frac{9}{x^2} = 12 \] Multiplying the entire equation by \(x^2\) (assuming \(x \neq 0\)) yields: \[ 9x^5 - 12x^2 + 9 = 0 \] This is a polynomial equation we can solve for \(x\). By trying rational roots or factoring, we find \(x = 1\). Then: \[ y = -\frac{3}{1} = -3 \] Now substituting \(x = 1\) back into \( (3x + p)^2 \) requires knowing \(p\). Assuming \(p\) is a constant given, we can evaluate \( (3 \cdot 1 + p)^2 = (3 + p)^2\). For the second part with \(m\): Given \(x y^2 = 4\) and \(x^3 - 2x^2y = 3\), we can express \(y\) from the first equation as \(y^2 = \frac{4}{x}\). Substituting \(y = \sqrt{\frac{4}{x}}\) into \(x^3 - 2x^2y = 3\): \[ x^3 - 2x^2 \sqrt{\frac{4}{x}} = 3 \\ x^3 - 4 \sqrt{x} = 3 \] This equation can lead us to find values for \(x\). Solving \(x^3 - 4\sqrt{x} - 3 = 0\) may be challenging but leads us to possible values for \(m\). We discover \(x = 4\) fits, giving \(y^2 = 1\) (so \(y = 1\) or \(-1\)). The first equation works out, and finally, substitute \(x = 4, y = 1\): \[ m = 4(4-1)^2 = 4(3^2) = 4 \cdot 9 = 36. \] Thus, the value of \(m\) is \(36\).

Related Questions

Latest Algebra Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy